Considering Sampling Methods for Macrofungi Exploration in Turgo Tropical Forest Ecosystem - Dwiki Prasetiya Prayudi; Junita Kurniawati; Yuni Prastiwi Mutiarani; Ishadiyanto Salim; Tien Aminatun (Universitas Gadjah Mada, 2019)
Diversity of macrofungi is widely studied because of its role as decomposer, and highly reported of its potentially using for foods, agricultures, medicinal purposes, and bioremediation. This study was carried out to consider sampling methods for macrofungi exploration especially in Turgo tropical forest ecosystem. There were two sampling method models which adequately bring our macrofungi collection to have valid data. The first is adaptive sampling which includes fixed-size plots where prior we decided how many tracks, plots, or what size to examine at each site to help keeping our focus on track. By having a fixed plot, we allowed ourselves to find our macrofungi and work on the identification process thoroughly without racing against the time as much. Then we can obtain frequency, distribution, density and others ecological quantitative data by sampling plots. Another way, we can choose opportunistic sampling, we mean carefully walking on through chosen site as study area and collecting conspicuous sporocarp of macrofungi. This method needs no plots and does not produce any quantitative data but looking for many more diversity on macrofungi. The way of sampling, depends on the duration of observation and the purposes of the research. According to the consideration result, we concluded to choose the adaptive sampling method to explore the macrofungi in Turgo tropical forest ecosystem.